Socioeconomic burden of participation in clinical trials in patients with myeloproliferative neoplasms. (5th May 2017) - Goel, Swati; Paoli, Chiara; Iurlo, Alessandra; Pereira, Arturo; Efficace, Fabio; Barbui, Tiziano; Tefferi, Ayalew; Vannucchi, Alessandro M.; Cervantes, Francisco
Abstract: Objective: To determine the financial and psycho‐social impact of participation in clinical trials of patients with BCR/ABL ‐negative myeloproliferative neoplasms (MPN). Methods: An international, observational cross‐sectional study was performed in 143 consecutive MPN patients (51% myelofibrosis, 36% polycythemia vera, 13% essential thrombocythemia), 68% from Italy, 17% from USA, and 15% from Spain. Results: Thirty‐five percent of patients reported having spent more money during the trial than in previous treatments and 21% having missed more workdays. Twelve percent replied that they would not have participated in the trial if the financial consequences would have been known beforehand. In 10% of the patients, the interpersonal relationships were more affected during the trial than in previous treatment but, overall, 91% subjects believed that participating in the clinical trial was worth the financial or emotional suffering. Concerning patients' suggestions, 54% of them indicated that the number of visits required for the trial should be clearly specified in the informed consent, 60% recommended travel cost reimbursement, and 23% hotel cost reimbursement. Conclusions: Physicians and pharmaceutical companies involved in clinical trials with patients with hematological diseases should be aware of these problems and make efforts to attenuate the socioeconomic burden of participation in the trials.